Good teaching practices: Re-examining curricula, materials, activities, assessments - KC Lee; Jenny Scoles (University of Johannesburg, 2020)
Issue 4.2 presents 11 full articles, two reflections, and three book reviews from a diverse teaching and learning contexts in terms of discipline, dynamics of students and classroom, region, approach, and so on from Afghanistan, Kenya, New Zealand, Rwanda, Singapore, South Africa, Zambia, Pakistan, United Kingdom, Uganda, and United States. Separately yet together, these publications provide a timely reminder to us to re-examine what we are doing in our classroom beyond and despite the COVID-19 pandemic. They surface issues that affect student experience and success such as accessibility, equality, diversity, fairness - all of which are what Leibowitz identifies as issues confronting the global South (2017).